Schisandrin A inhibits dengue viral replication via upregulating antiviral interferon responses through STAT signaling pathway - Yu, Jung-Sheng (Sci Rep, 2017)
Dengue virus (DENV) infects 400 million people worldwide annually. Infection of more than one serotype of DENV highly corresponds to dengue hemorrhagic fever and dengue shock syndrome, which are the leading causes of high mortality. Due to lack of effective vaccines and unavailable therapies against DENV, discovery of anti-DENV agents is urgently needed. We first characterize that Schisandrin A can inhibit the replication of four serotypes of DENV in a concentration- and time-dependent manner, with an effective half-maximal effective concentration 50% (EC(50)) value of 28.1 ± 0.42 μM against DENV serotype type 2 without significant cytotoxicity. Furthermore, schisandrin A can effectively protect mice from DENV infection by reducing disease symptoms and mortality of DENV-infected mice. We demonstrate that STAT1/2-mediated antiviral interferon responses contribute to the action of schisandrin A against DENV replication. Schisandrin A represents a potential antiviral agent to block DENV replication in vitro and in vivo. In conclusion, stimulation of STAT1/2-mediated antiviral interferon responses is a promising strategy to develop antiviral drug.